PERBANDINGAN NILAI ARUS JENUH PADA PENDEKAT SIMPANG DENGAN DAN TANPA RUANG HENTI KHUSUS - Fadli, Syaiful; Elkhasnet, Elkhasnet (Jurnal Transportasi, 2012)
Stacking of vehicles trouble especially motorcycles often happens to pass through the intersection stop line. Advanced Stop Area (ASA) for motorcycles is one of treatment to solve the problem.The purpose of this study is to compare values of saturated flow on the approach of intersections with and without ASA. The survey was conducted on the 4th to the 7th of June, 2012 at 16:00 to 18:00 at the intersection of Ahmad Yani Laswi, Pasteur-Sukajadi and Ir. H. Juanda - Surapati for the intersection with ASA and intersection of Gatot Subroto-Laswi and Ir. H. Juanda-Sulanjana for intersections without ASA in Bandung. Saturated flow for 9 m width protected with ASA is 4355 pcu/gh and without ASA is 4034 pcu/gh. The intersection with 9 m width of opposed with ASA is 4941 pcu/gh and without ASA is 4605 pcu/gh. The intersection with a width of 6 m opposed with ASA is 3427 pcu/gh and without ASA is 3255 pcu/gh. ASA will increase the value of saturation flow at 8% for protected intersection and 7.3% for opposed intersection width of 9 m, and 5.3% for opposed intersection width of 6 m. Influence the application of ASA at an intersection approach will be obvious to the departure of the data in units of vehicles, especially motorcycles units.Keywords: intersection, saturated flow, Advanced Stop Area (ASA)